ANALISIS IMPLEMENTASI PENGELOLAAN ARSIP ELEKTRONIK DI SENTRAL ARSIP PT. SEMEN PADANG SUMATERA BARAT - Yulia Permata Sari (Jurnal Ecogen, 2018)
Implementation of electronic archive management (e-archives) in the Central Archives of PT. Semen Padang has not been carried out optimally, due to limited human resources and requires a long time in the archives. The purpose of this study was to determine the implementation of electronic archive management in the Central Archives of PT. Semen Padang. The method used is Qualitative Descriptive Research. Determination of Informants in this study was carried out with Snowball Sampling Technique, so that the informant was directed to an archive storage room. Data collection is done through Observation, Interview and Documentation, with Model Data Analysis Techniques of Miles and Huberman. The findings in this study indicate that (1) the process of managing electronic records is not in accordance with the proper regulations; (2) do not have standard provisions in carrying out an electronic archive storage system; (3) the process of implementing electronic records management has not run optimally. Keyword: Analysis, Implementation, Archive Management, Electronic Archives